Eksistensi Cafe dalam Tren Cafe Hopping Sebagai Pengembangan Aktivitas Urban Tourism di Banyuwangi - Dita Ayu Lestari; Ryan Yeremia Iskandar; Arya Putra Sundjaja (Economic Reviews Journal, 2024)
Tourism activities in urban areas in Banyuwangi are currently experiencing limitations where it is currently very difficult to find tourist attractions in exploring urban tourism in the Banyuwangi area that are attractive to tourists. The development of tourist attractions to increase urban tourism activities in Banyuwangi or Urban Tourism is carried out by exploring the potential that exists in urban areas. The current trend of café hopping has become a new phenomenon that offers interesting activities in urban areas, namely visiting cafés and restaurants at close intervals. This trend not only increases urban tourism activities for tourists but also develops the existence of cafes and restaurants visited by tourists. This research data was collected using observation methods, in-depth interviews with informants. Informants are determined based on purposive sampling, where informants are selected based on certain specifications. The informants for this observation were the staff and managers of the Banyuwangi International Yacht Club, Casa Banyu, Alas and Sarasa. The results of this research analyze the tourist attraction of each café and restaurant that is the destination of the café hopping trend, and the development of each café and restaurant since the emergence of the café hopping trend. The development of cafés and restaurants was analyzed using fishbone analysis to see the impact on each café and restaurant of the café hopping trend as one of the urban tourism activities in Banyuwangi.